Damage detection in quasi-isotropic composite bends using ultrasonic feature guided waves - Yu, Xudong (2017)
Complex-shaped composite components have been extensively incorporated as reinforcing structures in the aerospace industry. Various types of damages can be initiated in these structures due to the stress concentration and out-of-plane impacts during the in-service use, which have to be detected timely in case they propagate at subsurface laminae and ultimately lead to catastrophic failure. This paper explores the feasibility of using ultrasonic feature guided waves (FGW) for rapid screening of typical 90° bends made of quasi-isotropic composite laminates. Such FGWs are capable of focusing the propagation energy along the feature, with limited leakage to the adjacent plate. Modal studies of the composite bent plate are carried out by applying the Semi-Analytical Finite Element (SAFE) method, revealing properties of the FGWs that exist in the structure. A shear horizontal type bend-guided mode has been identified as a promising candidate. The mode is almost non-dispersive and non-leaky with strong energy confinement in the bend region, which is attractive to be applied as a screening tool for composite bends. Both 3D Finite Element (FE) simulations and experiments are performed to study the interaction of the identified FGW mode with different defects occurred in the bend region such as the interlaminar delamination and the transverse crack, showing good agreement. The wave-defect resonance phenomenon and the reflection behavior are investigated for localizing these two types of defects, and the potential of the FGW for efficient damage detection in composite bends is well demonstrated.